ANALISIS KINERJA KEUANGAN PEMERINTAH PADA BADAN KEUANGAN KABUPATEN LIMA PULUH KOTA - Safitri, Annisa Desi; Putri, Lodia Dwika; Zaharman, Zaharman (Jurnal Akuntansi Kompetif, 2023)
The purpose of this research is to find out and analyze the government's financial performance in the Fifty Cities Regency Finance Agency in 2017-2021 by using the ratio of degrees of fiscal decentralization, the ratio of independence, the ratio of PAD effectiveness, the ratio of efficiency, and the ratio of activity.The object of this research is the Budget Realization Report obtained from the Fifty Cities District Finance Agency, the type of data used is quantitative data in the form of a report on the realization of the Fifty Cities District budget for 2017-2021. Data sources are primary data and secondary data. Data collection techniques are observation, documentation, literature studies and interviews.The results of the study show that based on data analysis and discussion that has been carried out the government's financial performance at the Lima Puluh Kota Regency Financial Board seen from the Ratio of the Degree of Fiscal Decentralization and the Ratio of Regional Financial Independence are still in the "very less" category, the Effectiveness Ratio is in the "effective" category, the Ratio Efficiency in the "less efficient" category was only "efficient" with a percentage of 70% in 2018, the Activity Ratio in operating expenditures was in the "good" category, and in capital expenditures it was in the "bad" category. Keywords: Analysis, Financial Performance, and Government